Ethics and Imitatio Christi in 1 John: A Jewish Perspective - Leung, Mavis M. (Tyndale bulletin, 2018)
This paper focuses on one of the ethical features of 1 John, namely ‘the imitation of Christ’. It argues that this ethical feature is related to the believers’ identity and vocation as the people of God. Just as in the OT Israel is obliged to reflect God’s nature in everyday life, the believers must take on Jesus’ character as their character and follow in his footsteps to surrender one’s own life for the benefits of others. The result of this paper indicates that the weight of the Jewish ethical thoughts in the formation of Johannine ethics is more important than often acknowledged.